Exploring Social Exclusion in The European Union, a Quantitative Approach - Gavuliak, Roman (Comparative Economic Research. Central and Eastern Europe, 2013)
Social exclusion is a widely debated issue. Its definitions and perceptions vary. Within the paper we identify the underlying factors of social exclusion within the EUfor years 2005-2009 through the use of factor analysis. These factors are as such immeasurable by common indicators. Through factor scores we compare the severity of these factors in each EU 27 and suggest five categories of types of social exclusion.